Changing the calculated surface area of wood samples to define drying schedules for Eucalyptus clones - Daiane de Moura Borges Maria; Natalino Calegario; Bruno Charles Dias Soares; Dáfilla Yara Oliveira de Brito; José Tarcísio Lima (Maderas: Ciencia y Tecnología, 2022)
The aim of this study was to determine how varying the inputted surface area value of wood samples would affect the determination of kiln-drying schedules using the drastic drying test. For this purpose, eight individuals of two Eucalyptus clones were selected. Specimens were obtained for drastic drying tests at 100 °C, to measure the basic density and to determine the initial moisture content. The initial and final temperatures and the drying potential were calculated in 100 mm × 50 mm × 10 mm samples, considering the surface area to be 130 cm² (Updated Method), in contrast to the surface area of 100 cm² that is commonly used in the method known as the Standard Method. Based on these findings, kiln-drying schedules were set for the lumber from each clone. Although the significant differences aforementioned, it was observed that the drying schedules developed by Standard Method and Updated Method are similar.